PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Outsourcing Kantor PT Telekomunikasi Indonesia Tbk. Kandatel Kebumen) - Widiyanto, Darmawan; Nugraheni, Rini (Diponegoro Journal of Management, 2018)
The problem that can be known is that there is a decrease in performance every month. This is based on the number of employees who fall into the lower category every month continues to grow. Based on the research gap there are differences in results from one study with other research and from the phenomena that occur in the company. The existence of differences from these studies alleged motivational factors and job satisfaction have a significant factor on employee performance. This study aims to examine and analyze the influence of motivation on job satisfaction and the performance of outsourcing employees of PT Telekomunikasi Indonesia Tbk. Kandatel Kebumen then the mediation effect from job satisfaction on influence of motivation on performance.The population and sample used in this study are outsourcing employees of PT Telekomunikasi Indonesia Tbk. (PT Telkom) Kandatel Kebumen who currently works for more than one year, namely 53 people. The sampling technique used is a census. Data collection methods in this study use questionnaires and interviews. Data analysis method uses path analysis.Based on the results of research, motivation has a positive effect on job satisfaction and the performance of outsourcing employees of PT Telekomunikasi Indonesia Tbk. Kandatel Kebumen, while job satisfaction has a positive effect on the performance of outsourcing employees of PT Telekomunikasi Indonesia Tbk. Kandatel Kebumen. Based on the results of the Sobel Test to determine whether there is a mediating relationship between independent and dependent variables, it is known that satisfaction mediates the influence of work motivation on employee performance.